Experimental infection by Brucella ovis: Changes in NTPDase, 5’-Nucleotidase and Acetylcholinesterase Associated Cerebral Oxidative Stress - Perin G.* (2019)
© 2019 Universidade Federal do Rio Grande do Sul. All rights reserved.Background: Changes in purinergic and cholinergic signaling have been demonstrated in various pathologies associated with inflammation; however, the changes in brucellosis caused by the Gram-negative coccobacillus Brucella ovis are not known. B. ovis is generally asymptomatic in ewes. Hepatosplenomegaly has been described in B. ovis, a non-zoonotic species, characterized by an extravascular inflammatory response. Purinergic system enzymes are closely involved with the modulation of the immune system, pro- and anti-inflammatory events. The objective of this study was to investigate the role of ectonucleotidases and cholinesterase’s in the brains of mice experimentally infected with B. ovis. Materials, Methods & Results: Forty-eight animals were divided into two groups: control (n = 24) and infected (n = 24). In group infected, 100 µL containing 1.3 x 107 UFC B. ovis /mL via intraperitoneal was used in inoculation. The brains were collected from the animals on days 7, 15, 30 and 60 post-infection (PI). We measured levels of TBARS (substances reactive to thiobarbituric acid) and ROS (reactive oxygen species) in the brain. The activity of NTPDase (using ATP and ADP as substrate) and 5’-nucleotidase (using AMP as substrate) were evaluated in brain in addition to histopathological analysis. No histopathological lesions were observed in the control group nor the infected group at days 7, 15, and 30 PI. However, multifocal areas with moderate microgliosis in the cerebral cortex were observed at day 60 PI in the infected animals. B. ovis DNA was detected in brain. During the course of infection, B. ovis caused greater lipid peroxidation in the brains of infected animals than in the control group at day 60 PI. No significant results were observed at 7, 15 or day 30 PI. Similarly, there was significantly more reactive oxygen species at day 60 PI in brains of infected animals than in the control group. NTPDase activity (using ATP and AMP as substrate) was lower at days 7 and 15 PI in infected animals than in control. However, during the course of infection there was an increase in NTPDase activity at day 60 PI in the infected group. The infected animals showed a decrease of 5´-nucleotidase (AMP as substrate) activity at days 7 and 30 PI. On the other hand, 5’-nucleotidase activity was greater on day 60 PI in the experimental group than in the control. The results suggest that nucleotide hydrolysis was low in the acute phase (up to day 30 PI) due to the decrease of NTPDase and 5´-nucleotidase activities. After day 60 PI, there was a reversal in enzyme activities, probably with concomitant increase of extracellular nucleotides. AChE activity in brain on days 30 and 60 PI compared to control. Discussion: Among the functions of NTPDase are inhibition of platelet aggregation, vascular homeostasis, modulation of inflammation and immune response, all via its regulation of extracellular concentrations of ATP, a pro-inflammatory molecule. E-NTPDase plays an important role in controlling lymphocyte function, including antigen recognition and activation of cytotoxic T cell effector functions, as well as the generation of signals. The enzyme E-5´-nucleotidase also exerts non-enzymatic functions, including induction of intracellular signaling and mediation of cell-cell adhesion and cell-matrix and migration. Levels of acetylcholine are regulated by cholinesterase enzymes that are present in cholinergic and noncholinergic tissues, as the acetylcholinesterase (AChE) is a membrane-bound enzyme, primarily found in the brain and cholinergic neurons, where it participates in the structural regulation of postsynaptic differentiation. The results demonstrated that the chronicity of infection by Brucella ovis causes oxidative damage in the brain, as well as modulation of ectonucleotidases and AChE activities.